Development of legal competence of employees in the process of managing a social institution at the modern stage - Armeiskyi, O. (Problems of Engineer-Pedagogical Education, 2019)
The article covers one of the most topical issues of developing legal competence of employees in the process of managing social institutions, which is able operatively to recreate the normatively-legal changes in the environment. One of the most important questions concerns the level of professional competence of modern leaders of educational institutions, with new requirements being imposed in relation to their personality and professional qualities and special attention being paid to development and self-development of legal competence. Therefore, in case every person exercises his/her rights, carries out duties, bears responsibility for actions, level of his/her legal competence, undoubtedly, appears to be different, depending on the level of knowledge in the field of law, skills, level of legal culture, which greatly affects his/her behavior in certain legal relationships. Scientists also underline that, in the sphere of education, there are legal relationships which are regulated by the norms belonging to different fields. The norms of the educational law regulate relations that arise "inside" the educational process and are connected with its organization and realization. Other types of legal relationships in the field of education are linked to the necessity of the material, personnel, financial and other provisions for activities directed at achieving educational aims and tasks. These relations are regulated by the norms of the corresponding fields of law, i.e. labour law (recruiting pedagogical workers and signing employment agreements (contracts), choosing working hours, etc.); civil law (establishing organizational and legal forms of educational institutions, signing commercial contracts, providing chargeable educational services, protecting personal non-property rights, etc.); administrative management and control law (attestation of pedagogical workers, licensing and accreditation of activities of educational institutions, etc.); financial law (financial support for activities of educational institutions, public welfare (providing benefits and help for subjects of educational relationships, etc.). Pedagogical workers should easily navigate a large variety of legal relations arising in their professional activity, which stipulates the necessity of restructuring them with the aim Therefore, the content of legal competence development among employees in the process of managing a social institution must mirror the current state of legal regulations in both the field of education and other fields of law whose norms are reflected in professional activity of these specialists; be founded on theoretical bases of law, occupational safety and ergonomics; be formed on the basis of their experience of professional-legal activities; envisage some opportunities for employees to independently develop the abovementioned competence in the process of managing a social institution. of their system presentation within the legal competence content.